Shuangshen Granules Suppress Myeloid-derived Suppressor Cell-mediated Lung Premetastatic Niche Development by Targeting Sphingosine-1-Phosphate Receptor-1/Signal Transducer, Activator of Transcription 3 Signaling - Rui Liu; Jia-Qi Hu; Xing Zhang; Xiao-Yi Wu; Hua-Min Wei; Yuan-Chen Zhao; Shu-Lin He; Jing Yu; Xin Qi; Ying-Xia Pei; Hong Chen; Wei-Dong Li; et al. (World Journal of Traditional Chinese Medicine)
Background: Shuangshen granules (SSGs) are extensively utilized for the treatment of lung cancer in China and have been reported to possess tumor-protective and anti-metastatic effects. Therefore, it is crucial to understand the precise mechanism. Building upon the findings of our previous study, the objective of the present study was to explore the impact of SSGs on the sphingosine-1-phosphate receptor-1 (S1PR1)/signal transducer and activator of transcription 3 (STAT3) axis, as well as the recruitment of myeloid-derived suppressor cells (MDSCs) during the formation of the premetastatic niches (PMNs). Methods: In a mouse xenograft model utilizing Lewis lung carcinoma (LLC) cells that express green fluorescent protein (GFP), the initiation of lung metastasis was monitored every three days until day 35 following transplantation. Lung metastasis, MDSC recruitment, the expression of PMN and S1PR1/STAT3 axis biomarkers, as well as the blood levels of granulocyte-macrophage colony-stimulating factor (GM-CSF) and transforming growth factor-β (TGF-β) were assessed in the SSG treatment and control groups. Results: The LLC cells did not reach the lung until 14–17 days following subcutaneous implantation, which was concurrent with the formation of lung PMNs. SSG significantly postponed the initiation of lung metastasis and reduced the recruitment of MDSCs to the lung PMNs. SSG also suppressed the S1PR1/STAT3 axis in tumor tissues, bone marrow, and lung PMNs. Additionally, SSG suppressed the blood levels of GM-CSF and TGF-β, as well as the PMN markers, matrix metalloproteinase-9 and versican. Conclusion: Our findings suggested that SSG suppressed the development of MDSC-mediated PMNs by inhibiting the S1PR1/STAT3 axis, consequently postponing the initiation of lung metastasis.